PERANCANGAN KENDALI OPTIMAL PLTN TYPE PWR (PRESSURISED WATER REACTOR) DENGAN METODA D-POLE ASSIGNMENT - K S A L, I
Abstract : In design of optimal control system, one of most important problems that designers dealing with is selection of Q and r weight matrix. That is how to select such the matrix so not only optimal qualitification is fulfilled, but also qualitification of dynamic characteristic which is consistent with specification. In solving the problem, K. Furuta and S. B. Kim from Tokyo Institute of Technology, by 1987, have succeded to develop a method of selecting the weight matrix called as \"D-Pole Assignment\" method. It is in principle designed to put the poles of closed circle system into a chircle-shaped zone with certain center and radius, which as then called as the \"D-zone\". In order to facilitate the design process, \"D-Pole Assignment\" method was applied in this theses for design of discrete optimal control at z-plane. This theses also examines computation procedur of respond matrix to Riccati. P equation, F1 feedback vector, and Q weight matrix through the form of canonical fase variable. Bacause the computation procedures of P, Q and Ft by \"D-Pole Assignment\" will difficult to be done as a result of A and B matrix which are in common form. Then the produced design procedure is applied into dynamic simulation of PLTN type PWR (Pressurised Water Reactor). The simulation performed to the control system of boiling water temperature within secondary circle of reactor, since the main effect of reactivity in reactor is caused by the temperature change. Furthermore simulation is conducted by means of investigating ,effect of citating period selecting on location of polies in the closed circle, and effect of change in \"D-Zone\" center on dynamic respond and the use of control energy in closed circle system. Generally, from the simulation can be concluded that stability system became stronger when location of \"D-Zone\" center more and more close to unit circle center in z-plane. In order to include all poles the of the closed circle system. into \"D-Zone\" then limits of center (a) radius (r2) of the \"D-Zone would ibe 0,025 < a < 0,40 and r2 = 0.40 resvectively.